Performance of dental undergraduate students using International Caries Detection and Assessment System (ICDAS) / Noorharliana Mohamed Zohdi ... [et al.] - Mohamed Zohdi, Noorharliana; Nasruddin, Mohd Faiz; Sanusi, Muhammad Aiman; Nordin, Muhammad Atep; Rusli, Mohamad Rahmatullah (Faculty of Dentistry, Universiti Teknologi MARA, 2020)
This study aimed to assess intra- and inter-examiner reliability of International Caries Detection and Assessment System (ICDAS) and modified epidemiology ICDAS (MOD) code by undergraduate dental students with different clinical experiences. A total of 150 dental undergraduate students with varying clinical experiences (0, 1 and 2 years of clinical experience) were recruited. Participants received training through a theoretical lecture on ICDAS criteria by an experienced National Benchmark Group (NBG) examiner and underwent e-learning program prior to ICDAS calibration. Visual examination on extracted permanent teeth (N= 45) with different location and stages of caries progression ranging from ICDAS scores 0 to 6, was performed using the ICDAS criteria. The assessments were repeated after one hour. The data were analysed to evaluate inter-examiner and intra-examiner reliability in the form of kappa scores using SPSS 23 Software. Mean kappa values for intra- and inter-examiner reliability for ICDAS code, were between 0.41 to 0.60, and 0.61 to 0.80 respectively. For MOD code, mean kappa values for intra- and inter-examiner reliability were between 0.61 to 0.80. Good intra-examiner agreement (>0.61) was observed in both ICDAS and MOD code for all groups. All students performed similar agreement, therefore, clinical experience within 2 years does not influence the performance of visual inspection in detecting caries using ICDAS. The results of the study shows that ICDAS and modified epidemiology ICDAS codes has good reproducibility and is feasible to be used as a tool in clinical practice as well as patient education.